Role of exosomes in exacerbations of asthma and COPD: a systematic review - Laitano, Rossella; Calzetta, Luigino; Motta, Enrico; Puxeddu, Ermanno; Rogliani, Paola (Frontiers in Molecular Biosciences, 2024)
Asthma and chronic obstructive pulmonary disease are chronic respiratory disorders characterized by airways obstruction and chronic inflammation. Exacerbations lead to worsening of symptoms and increased airflow obstruction in both airways diseases, and they are associated with increase in local and systemic inflammation.Exosomes are cell-derived membrane vesicles containing proteins, lipids, and nucleic acids that reflect their cellular origin. Through the transfer of these molecules, exosomes act as mediators of intercellular communication. Via selective delivery of their contents to target cells, exosomes have been proved to be involved in regulation of immunity and inflammation. Although, exosomes have been extensively investigated in different diseases, little is currently known about their role in asthma and COPD pathogenesis, and particularly in exacerbations. This review aims to systemically assess the potential role of exosomes in asthma and COPD exacerbations.